The Effect of Emotional Intelligence, Workload, and Work Stress on Employee Performance at PT Berlimpah Anugerah Sejati Denpasar - Kadek Bertha Widyani Putri; I Gede Rihayana; Bagus Nyoman Kusuma Putra (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2026)
In order to create innovations that can improve the competitiveness and quality of a company, the development and improvement of employee performance must be a top priority for the company. One factor that can affect employee performance in a company is emotional intelligence. The ability to manage emotions enables employees to continue to carry out their responsibilities professionally even under pressure. Another factor that can affect employee performance is workload. The workload assigned to employees must be balanced with their competencies and abilities; otherwise, sooner or later, it will cause problems that can disrupt employee performance. Another factor that affects employee performance in a company is work stress. Employees who experience stress will generally experience a decline in performance due to mental tension. The purpose of this study is to examine and analyze the influence of emotional intelligence, workload, and work stress on employee performance. This research was conducted at PT Berlimpah Anugerah Sejati, located at Jl. Cargo Permai No.9X, Ubung, Kec. Denpasar Utara, Kota Denpasar. The population in this study was all 36 employees of PT Berlimpah Anugerah Sejati Denpasar. Considering that the population in this study was less than 100, the sampling technique used was saturated sampling. The data analysis technique used was multiple linear regression analysis. The results showed that emotional intelligence had a positive and significant effect on employee performance, workload had a negative and significant effect on employee performance, and work stress had a negative and significant effect on employee performance.